2013
DOI: 10.1111/iwj.12143
|View full text |Cite
|
Sign up to set email alerts
|

Vessel transformation in chronic wounds under topical negative pressure therapy: an immunohistochemical analysis

Abstract: The underlying physiological mechanism of topical negative pressure (TNP) therapy is not yet completely understood. This prospective clinical study aims to clarify a potential influence of TNP therapy on vessel proliferation and hypoxia in chronic wounds. TNP was applied on chronic wounds of 16 patients (-125 mmHg) to prepare them for a plastic-surgical reconstruction using free or pedicled flaps. Tissue biopsies were taken from the wound edge and wound bed at different time points. All samples were stained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Nelson et al, 24 Lance et al, 29 and Qiu et al 34 some experimental studies have proven that NPWT can increase skin perfusion and boost circulation by various mechanisms. 12,15,42,43 Furthermore, two articles included in this review reported that vascular pedicle and flap perfusion were not compromised by NPWT even at a high-pressure setting of NPWT. 25,27 More studies are needed in the future to validate the influence of NPWT on flap perfusion.…”
Section: Discussionmentioning
confidence: 91%
“…Nelson et al, 24 Lance et al, 29 and Qiu et al 34 some experimental studies have proven that NPWT can increase skin perfusion and boost circulation by various mechanisms. 12,15,42,43 Furthermore, two articles included in this review reported that vascular pedicle and flap perfusion were not compromised by NPWT even at a high-pressure setting of NPWT. 25,27 More studies are needed in the future to validate the influence of NPWT on flap perfusion.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, endothelial cells were shown to contribute to vascular remodeling though their transformation into mesenchymal or SM-like phenotype cells that then migrate into their underlying tissues. Other studies also indicated that endothelial cell transformation can occur in adult life during a number of diseases, including PAH [3], atherosclerosis [4] and wound healing [5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this variability, an underlying process of wound pathogenesis has evolved through the study of chronic wound care that involves local tissue hypoxia, bacterial colonisation and host inflammatory response, repetitive ischemia–reperfusion injury, and altered cellular or systemic response that occurs with ageing or other comorbidities . Successful therapies in the treatment of chronic wounds have been shown to improve tissue oxygenation within devitalised tissue . Therefore, optimisation of perfusion is a major target for medical therapy in the pathogenesis of chronic wounds and their complications.…”
Section: Discussionmentioning
confidence: 99%